Histomorphological spectrum of eyelid lesions–A 6 year retrospective study - Dr. Giri Punja M; Dr. Bharathi M.; Dr. Shashidhar H.B. (Tropical Journal of Pathology and Microbiology, 2018)
Background: Eyelid lesions are encountered by all primary care physicians and Ophthalmologists. Histology of eyelid comprises various components and structures that give rise to a wide spectrum of pathologies. The clinical presentation of eyelid lesions is myriad with benign lesions masquerading malignant tumours. Though eyelid lesions are fairly common in Indian subcontinent, there is paucity of reports in Indian literature. This study was undertaken to characterize the distribution of various eyelid lesions and clinicopathological correlation in a tertiary care centre of South India.Objectives: To retrospectively carry out a clinicopathological analysis of eyelid lesions requiring surgical excision in the Department of Pathology of a tertiary care centre in South India.Methods: A retrospective review of clinicopathological profile of excised eyelid lesions diagnosed in our tertiary care centre was done. Clinicopathological data were retrieved from patient’s clinical records and biopsy reports.Result: Among 219 eyelid lesions, 192 were benign lesions and 27 were malignant tumours. The most common eyelid lesion was dermoid cyst (69 cases) followed by Nevus (32 cases) and Pyogenic Granuloma (12 cases). The most common malignant eyelid lesion was Sebaceous Cell Carcinoma (13 cases).Conclusion: Dermoid cyst and Nevus are the most common eyelid lesions requiring biopsy and sebaceous cell carcinoma is the most common malignant eyelid tumour. All surgically excised eyelid lesions must be subjected to histopathological examination without fail to provide a definitive diagnosis, continued patient care and management.